Nanostructured transdermal hormone replacement therapy for relieving menopausal symptoms: a confocal Raman spectroscopy study - Marco Antonio Botelho; Dinalva Brito Queiroz; Gisele Barros; Stela Guerreiro; Pierre Fechine; Sonia Umbelino; Arao Lyra; Boniek Borges; Allan Freitas; Danilo Caldas de Queiroz; Ronaldo Ruela; Jackson Guedes Almeida; et al. (Clinics, 2014)
OBJECTIVE: To determine the safety and efficacy of a transdermal nanostructured formulation of progesterone (10%) combined with estriol (0.1%) + estradiol (0.25%) for relieving postmenopausal symptoms. METHODS: A total of 66 postmenopausal Brazilian women with climacteric symptoms of natural menopause received transdermal nanostructured formulations of progesterone and estrogens in the forearm daily for 60 months to mimic the normal ovarian secretory pattern. Confocal Raman spectroscopy of hormones in skin layers was performed. Clinical parameters, serum concentrations of estradiol and follicle-stimulating hormone, blood pressure, BI-RADS classification from bilateral mammography, and symptomatic relief were compared between baseline and 60 months post-treatment. Clinicaltrials.gov: NCT02033512. RESULTS: An improvement in climacteric symptoms was reported in 92.5% of women evaluated before and after 60 months of treatment. The serum concentrations of estradiol and follicle-stimulating hormone changed significantly (p<0.05) after treatment; the values of serum follicle-stimulating hormone decreased after 60 months from 82.04±4.9 to 57.12±4.1 IU/mL. A bilateral mammography assessment of the breasts revealed normal results in all women. No adverse health-related events were attributed to this hormone replacement therapy protocol. CONCLUSION: The nanostructured formulation is safe and effective in re-establishing optimal serum levels of estradiol and follicle-stimulating hormone and relieving the symptoms of menopause. This transdermal hormone replacement therapy may alleviate climacteric symptoms in postmenopausal women.